The influence of dietary threonine on growth performance and carcass characteristics of pST-treated finishing pigs - J L Laurin; J A Hansen; B R Schricker; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1991)
Eighty crossbred barrows (initial wt = 131 lb) were utilized to determine the dietary threonine requirement of finishing pigs injected with porcine somatotropin (PST). Barrows were injected daily in the extensor muscle of the neck with either 4 mg pST or a placebo and fed diets containing either .45, .55, .65, or .75% threonine. All other amino acids, vitamins, and minerals were calculated to be at least double current requirements for finishing pigs so as not to limit performance. Pigs were housed in an open-sided building with two pigs per pen and five replications of the eight treatments. Feed and water were provided ad libitum. When the mean weight of the two pigs per pen averaged 235 +1- 5 lb, pigs were slaughtered and carcass data collected. Porcine somatotropin-treated pigs had greater average daily gain (ADG), reduced daily feed intake (ADFI), and improved feed efficiency (F/G) compared to control pigs. A dietary threonine X pST interaction was observed for ADG. Control pigs exhibited no improvement in ADG with increasing dietary threonine. However, pST-treated pigs had a 22% increase in ADG as dietary threonine increased from .45 to .65%. Increasing dietary threonine resulted in increased ADFI, but had no effect on F/G. Average backfat thickness, tenth rib fat depth, and kidney fat were reduced by pST administration. Longissimus muscle area and trimmed ham and loin weights were greater in pST treated pigs. Dietary threonine tended to reduce average backfat thickness but had no effect on other carcass criteria measured. These results suggest that growth rate of pSTtreated pigs is increased by dietary threonine level compared to control pigs. This interactive response between pST and threonine was not observed in feed efficiency or carcass criteria measured; however, there were numerical trends similar to those observed for daily gain.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; G-F; Performance; Threonine; Repartition; Carcass